Peningkatan Mutu Sekolah Melalui Program Unggulan Berbasis Keagamaan - Titi Kurniati (Jurnal Kependidikan, 2021)
Improving the quality of schools can be through superior programs. There are many excellent programs, one of which is based on religion. The flagship religious-based program carried out at SMP Negeri 1 Kedungbanteng, Banyumas Regency includes 1) the full day school system, which adds religious material in the curriculum content that is integrated in curricular, co-curricular and extracurricular activities. 2) education programs based on local excellence, namely through activities religious studies, namely the study of books and reading and writing of the Qur'an which ends with the Khotmil Qur'an activity which is a sign that students have completed the Qur'an. 3) Life skills education programs, including personal, social, academic, and vocational life skills . This activity is in the form of skills in writing and reading the Qur'an, making calligraphy, the art of reading the Qur'an, and the ability as a small preacher through extracurricular activities khitobah, 4) Graduate quality improvement programs, namely Increasing faith and piety through habituation activities such as tadarus Al-Qur'an, dhuha prayer, dhuhur prayer in congregation of Hajj Manasik activities, Spensa Bersholawat, and Istighosah before the School Exam. The success of the flagship religious-based program cannot be separated from the principal's role as manager, namely planning, organizing and controlling.